Level of Preparedness for Managing Crisis Communication on Land-Grant Campuses - Larry R. Whiting; Mark Tucker; Sherrie R. Whaley (Journal of Applied Communications, 2004)
Crisis situations can occur in any organization. Because they attract media attention and public scrutiny, crises demand effective intervention and response. Despite their importance, there has never been an inventory of crisis communication readiness at land-grant universities. This study used mail survey techniques to query communication administrators at 1862 and 1890 U.S. land-grant colleges of agriculture as to the level of preparedness that exists for handling crisis situations at their institutions. A major finding was that only about 60 percent of land-grant universities have a central crisis communication plan. Nearly one third of the respondents were unaware of a crisis communication plan at their university. Official crisis plans were most often found at the university level, followed by extension. Experiment station crisis plans were reported by fewer than one fourth of respondents, an alarming finding since research programs and facilities are considerably more susceptible to public outcry or threats from fringe groups. It was determined that faculty and staff are often not aware of crisis plans in place at their institutions and that communication professionals have limited involvement in the development of such plans. Findings highlight the need for communication professionals to be more proactive in assuring that crisis communication plans are in place and that they are involved in their development.